Synthesis of Maternal Resilience: Musical Representation of Mothers as Family Pillars after Divorce through Talempong Gua Cak Din Din - Betmon Oktivi Paulin (Melayu Arts and Performance Journal, 2025)
This study examines the artistic representation of mothers as the central pillars of family life after divorce through the creation of a contemporary Nusantara music composition based on talempong Gua Cak Din Din, a traditional Minangkabau musical practice characterized by interlocking rhythmic patterns. Responding to the limited scholarly attention on maternal resilience within artistic research frameworks, this study aims to analyze how musical structures can function as symbolic narratives of emotional endurance, role transformation, and social responsibility experienced by single mothers following divorce. Using an artistic research methodology, data were collected through in-depth interviews with divorced mothers, participant observation, and reflective compositional practice. These social experiences were translated into musical ideas through ethnomusicological analysis, narrative-symbolic interpretation, and technical-compositional experimentation. The creative process resulted in a three-part musical composition—Ketenangan (Calm), Runtuh (Collapse), and Mengakar (Rooted)—each representing distinct emotional and social phases in the post-divorce maternal journey. The findings reveal that the interlocking technique of talempong Gua Cak Din Din operates as an effective musical metaphor for the multiplicity of roles assumed by mothers after divorce. Gradual transformations in rhythm, texture, and dynamics reflect processes of emotional disruption, adaptation, and resilience. This study demonstrates that traditional musical idioms can be recontextualized to articulate contemporary social realities without losing their cultural integrity.This research contributes to the discourse on music-based artistic research, gender representation in performing arts, and the contemporary relevance of Minangkabau musical traditions. The novelty of this study lies in its integration of feminist cultural perspectives within a compositional framework, positioning music as both an aesthetic and reflective medium for social experience